Efforts to improve public health through the corona education center program in Karangrejo Village - Fitriana Yuliastuti; Ika Junia Safitri; Anggara Restu Aji; Sandra Andri Liana; Lina Anggraini; Athia Fidian (Community Empowerment, 2023)
The Coronavirus (Covid-19) outbreak has created a global health crisis that has had a profound impact on the way we understand the world and everyday life, and the people of Karangrejo Village are no exception. This service aims to increase knowledge and provide information to the public regarding the prevention of Covid-19. The activity was carried out in the form of the Corona Education Center Program which consisted of socialization and health education. At the end of the activity, all the elderly had received the second dose of the vaccine and the households included as healthy homes had been well identified. Apart from that, health education has proven to be effective in influencing behavior and increasing participants' knowledge in efforts to prevent the spread of Covid-19.